2017
DOI: 10.2147/tcrm.s138581
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio and mean platelet volume in central serous chorioretinopathy

Abstract: PurposeThis study aimed to evaluate mean platelet volume (MPV) and neutrophil/lymphocyte ratio (NLR) values and their relationship with clinical findings in patients with central serous chorioretinopathy (CSCR).MethodsOverall, 87 patients fulfilling inclusion criteria and 320 age- and sex-matched healthy individuals as controls were included in the study. The CSCR patients (n=87) were classified into 2 groups as acute CSCR (group 1, n=43) and chronic CSCR (group 2, n=44).ResultsIt was found that NLR (P<0.05) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…investigated NLRs and CRP levels in patients with acute or chronic CSC and found that both factors were significantly higher in patients with acute CSC than all others. [ 12 ] However, in multivariate analysis, NLRs and CRP values did not emerge as independent predictors of acute CSC. Their results are comparable with our findings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…investigated NLRs and CRP levels in patients with acute or chronic CSC and found that both factors were significantly higher in patients with acute CSC than all others. [ 12 ] However, in multivariate analysis, NLRs and CRP values did not emerge as independent predictors of acute CSC. Their results are comparable with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Since the pathogenesis of CSC is associated with systemic inflammation, some researchers have used a range of candidate biomarkers from peripheral blood to investigate the systemic inflammatory and oxidative status in patients with CSC. [ 12 14 26 27 ] In two studies, in particular, the thiol-to-disulfide ratio from peripheral blood samples was investigated as a biomarker of oxidative stress in patients with either acute or chronic CSC. [ 14 26 ] The results of both studies indicated that the thiol-to-disulfide ratio was significantly lower in patients with chronic or acute CSC when compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CSCR, Erol and colleagues have demonstrated that NLR and C-reactive protein (CRP) are higher in patients with acute CSCR when compared to normal volunteers and patients with chronic CSCR. [ 11 ] They also noted that, in chronic CSCR, mean platelet volume was higher. The present paper by Sirakaya et al .…”
mentioning
confidence: 97%
“…They did not observe any difference in CRP or ESR values, attributing it to small sample size; nor did another cited study. [ 2 ]…”
mentioning
confidence: 99%